Faktor-Faktor Yang Mempengaruhi Audit Delay Dengan Kantor Akuntan Publik Sebagai Variabel Moderasi Pada Perusahaan Manufaktur Yang Terpublikasi Di Bursa Efek Indonesia - Gymnastiar, Bagas Fauzan; Afifudin, Afifudin; Hidayati, Irma (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This to know examine the effect of audit tenure, profitability and audit opinion on audit delay which is moderated by the reputation of public accounting firms in manufacturing companies published on the Indonesia Stock Exchange for the 2020-2022 period. This type of research is descriptive correlational research with analytical method uses a quantitative analysis method using secondary data sourced through financial report documentation published by the Indonesian stock exchange. The research results reveal that Audit Tenure has a significant negative effect on Audit Delay. Profitability has a significant negative effect on Audit Delay. Audit Opinion has a significant positive effect on audit delay. The reputation of the Public Accounting Firm cannot moderate the relationship between Audit Tenure and Audit Delay. The reputation of the Public Accounting Firm cannot moderate the relationship between Profitability and Audit Delay. The reputation of the Public Accounting Firm cannot moderate the relationship between Audit Opinion and Audit Delay.Keywords: Audit tenure, profitability, audit opinion, the reputation of the public accounting firm, audit delay.